The Effect of Location, Price, Product Quality and Services in Improving the Reputation of Kristal Hotel: Social and Applied Statistics - Lena, Pratika Martha (The Eastasouth Management and Business, 2025)
This study will analyze the influence of location, price, and product/service quality on the reputation of Hotel Kristal, a four-star business hotel located in South Jakarta. A quantitative approach was used in this study with a sample size of 30 respondents. Data analysis was carried out using descriptive statistics, correlation analysis, and multiple linear regression through SPSS version 25. From the results of this study, it can be seen that the three independent variables significantly affect the dependent variable, with product/service quality having the strongest influence. The regression model explains 72% of the variation in reputation. These results emphasize maintaining high-quality service and utilizing strategic locations to enhance hotel reputation. This study also shows that effective pricing strategies are needed to attract and retain customers in a competitive market. Recommendations for hotel management and future research directions are also discussed.